Investigating the Properties of CIS Absorber Layer by Using the Spray Coating Method - Chien-Chen Diao; Cheng-Fu Yang; Chia-Ching Wu; Wen-How Lan; Yen-Lin Chen (International Journal of Photoenergy)
The CuInSe2 absorber layers were deposited on Mo/glass substrates by using the spray coating method (SCM). At first, the CIS powder was ground into nanoscale particles; then the 6 wt% CIS particles were dispersed into isopropyl alcohol (IPA) to get the solution for SCM. 0.05 mL CIS solution was sprayed on the 2 cm × 1 cm Mo/glass substrates, and then the CIS solution films were annealed in a selenization furnace under different parameters. At first, the extra 0.2 g Se was put in the furnace, the selenization time was 5 min, and the selenization temperature was changed from 450°C to 600°C. After finding the better selenization temperature of 550°C and setting the selenization time at 5 min, the selenization process was set at 550°C and the extra Se content was changed from 0 g to 0.6 g. The influences of the selenization temperature and extra Se content on the surface and cross-section morphologies, crystallization, hall mobility, and carrier concentration and resistivity of the CIS absorber layers were well investigated in this study.